Profile of the subclinical mastitis and frequency of microorganisms isolated from female crossbred buffaloes (Bubalus bubalis) (Research, Society and Development, 2022)
Mastitis is an inflammation of the mammary gland caused mainly by bacteria, being responsible for significant economic losses to dairy farming. The objective was to evaluate the profile of mastitis in dairy buffaloes and identify the main agents causing the infection. 45 female buffaloes (Murrah × Jafarabadi) were evaluated. Buffaloes with clinical mastitis were identified by the black bottom mug test, while subclinical mastitis was detected by the california mastitis test (CMT) and somatic cell count (SCC). Then samples of 50 mL of milk from infected animals were collected and, later, microbiological identification was performed by means of biochemical tests. The results showed that subclinical mastitis was prevalent in the herd studied. In CMT 48.88% of the animals were diagnosed with subclinical mastitis, and 51.11% were healthy. The posterior breast quarters had a higher frequency of subclinical cases (57.89%) than the anterior quarters (42.11%). SCC detected 73.33% of animals with subclinical mastitis (SCC ≥ 400,000 cells/mL) and 26.66% healthy (SCC < 400,000 cells/mL). Milk with subclinical mastitis had the highest mean SCC (51.3 × 103 cells/mL) than the healthy milk (23.9 × 103 cells/mL). The most frequent bacteria isolated was genus Staphylococcus spp. (35,29%), followed by Streptococcus spp. (20,00%), Escherichia coli (6,35%) and Mycoplasma spp. (4,54%). Therefore, improvements in health care for the control of subclinical mastitis in female buffaloes should be carried out. More research on mastitis in buffaloes should be carried out to support mastitis control programs in female buffaloes.